PRAKTIK KEWIRAUSAHAAN SOSIAL DALAM MENGATASI PERMASALAHAN MASYARAKAT DI KAMPUNG BADRAN RW XI KELURAHAN BUMIJO YOGYAKARTA - Etik Anjar Fitriarti; Bimantoro, Wajar (Jurnal Analisis Pendidikan Sosial, 2024)
The village of Badran is known as a preman village by the Yogyakarta community for decades ago. Adaptation of the image of the preman village is influenced by the social and economic situation of society. Social entrepreneurship is a form of effort to empower the society based on social issues present in a particular area. Social entrepreneurship can also be attributed to the impact and results that society can be strong or independent (economically). Social entrepreneurship in the village of Badran is a waste bank. capital loans production and savings activities to help micro-economic enterprises through Koperasi Amal Srikandi. This research use qualitative methods by conducting deep interview and observations. Adapting social entrepreurship activities in the village of Badran have gone well because it has benefited them. Keywords: social entrepreneurship, community empowerment, social problem, waste bank.